Effect of dietary supplementation of crude microalgal extracts on growth performance, survival and disease resistance of Lates calcarifer (Bloch, 1790) larvae - Gora, Adnan Hussain; Ambasankar, K.; Sandeep, K. P.; Rehman, Saima; Agarwal, Deepak; Ahmad, Irshad; Ramachandran, Kasilingam (Indian Journal of Fisheries, 2019)
The present study aimed to assess growth performance and health status of Lates calcarifer larvae fed with crude microalgal extracts. Larvae weighing 5.96 Â± 0.39 mg were randomly divided into four experimental groups in triplicates, with each replicate having 35 larvae. Four diets formulated to contain 55% protein and 12% lipid, were prepared with pigment rich microalgal extracts at 0% (T1) and 1% each of crude phycocyanin (T2), chlorophyll (T3) and astaxanthin (T4) extracts. The experiment was carried out in 30 l plastic tanks by feeding experimental diets to satiation. There was no significant difference (p